Validation of Xiphopenaeus dincao Carvalho-Batista, Terossi, Zara, Mantelatto & Costa and Xiphopenaeus baueri Carvalho-Batista, Terossi, Zara, Mantelatto & Costa (Decapoda: Penaeidae) from western Atlantic - Carvalho-Batista, Abner [UNESP]; Terossi, Mariana; Zara, Fernando J. [UNESP]; Mantelatto, Fernando L.; Costa, Rogério C. [UNESP] (Magnolia Press, 2020)
Two species of Penaeidae shrimp from western Atlantic were described by Carvalho-Batista et al. (2019) as Xiphopenaeus dincao and Xiphopenaeus baueri. The descriptions and figures presented by Carvalho-Batista et al. (2019) and the posterior author’s correction (Carvalho-Batista et al., 2020) characterize the species. However, the journal issue in which the description was published is online only, and the article with the new names did not include a ZooBank registration number (LSID), required for validation of new names in electronic-only publications (ICZN 2012). Thus, the names Xiphopenaeus dincao and Xiphopenaeus baueri, as published in Scientific Reports 9: 15281, is not available according the International Code of Zoological Nomenclature (ICZN 1999, 2012). Therefore, the present note serves to validate the names Xiphopenaeus dincao and Xiphopenaeus baueri by fulfilling ICZN conditions for nomenclatural availability. Type specimens of both species are deposited in Museu de Zoologia da Universidade de São Paulo (MZUSP), São Paulo, Brazil.